Kualitas Audit Memediasi Pengaruh Independensi Auditor dan Komite Audit terhadap Kualitas Laba - Suwito, Chandra Setiawan Darmo; Handajani, Lilik; Surasni, Ni Ketut (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
The purpose of this study is to analyze audit quality mediating the effect of the independence auditors and audit committees on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange 2015-2019. This research is a causality study with a quantitative approach. The research population was 144 companies which were selected to be 68 company samples. Dependent variable is earnings quality and the independent variable are independence of the auditor and the audit commitee and intervening variable is audit quality. This study uses path analysis. The results of the study found that audit quality did not mediate the effects of auditor and audit committee independence on earnings quality. The study found that supervision carried out by independent auditors and quality audits could hinder earnings management thereby increasing earnings quality. The audit committee was formed by the company as a formality to comply with government regulations. Keywords: Earnings Quality; Audit Quality; Auditor Independence; Audit Committee.